Engaging College Students in the Transition to Sustainability Through Design-Based Approaches - Mouchrek, Najla (Consilience, 2018)
To achieve social change towards sustainable ways of living, it is essential to promote a culture of sustainability among young people. Universities have a very important role, as sustainable education on college campuses has the potential to achieve long-term results by promoting the development of awareness and skills for youth engagement in order to face complex challenges, now and in the future. This study investigates the application of design-based thinking and participatory design to support a culture of sustainability among youth. It aims to bridge the value-action gap and to develop sustainable competencies. Design-based strategies integrated within educational experiences promote dealing with change and complexity, as well as offering a range of potentialities and interfaces for innovative action in the transition to sustainability. This research used a qualitative multi-method approach which consisted of a literature review, context analysis, ethnographic observation, and application of participatory design in educational settings in Brazil and the United States. This paper summarizes preliminary findings, including guidelines for engagement strategies. These reinforce the importance of understanding values and challenges of youth development, exploring dimensions of sustainability connected to student realities, building contexts for transformation, stimulating empowerment and autonomy, and using mediation to facilitate change processes conducted by young people. These findings also demonstrate that design-based participatory approaches in educational settings offer excellent opportunities for intervention to both engage youth in sustainability and support their positive development.